Growth hormone-Msp1 loci polymorphism and its association with first lactation traits in Sahiwal cattle - SACHAN, SHWETA; GUPTA, I D; VERMA, ARCHANA; VINEETH, M R; SINHA, REBEKA (The Indian Journal of Animal Sciences, 2020)
GH has important role in milk production and their polymorphisms may alter quality and quantity of gene's products and affects the phenotype. This study was designed to find the polymorphisms on GH-Msp1 loci and to find its association with milk production traits in Sahiwal cattle. Msp1 polymorphism of the bGH gene was identified in a population of Sahiwal cows. PCR-RFLP genotyping of 329 bp fragment of GH in exon 3 revealed three different allelic variants. The T allele was the major allele in Sahiwal cattle. The TT genotype Sahiwal cows yielded more FL305DMY, FLTMY and also had higher FLL than that of CT and CC genotypes cows. Results of the present findings reveal that TT allele of GH locus should be the favoured genotype in Sahiwal cattle breed and can be used in marker-assisted selection programmes.